Aplikasi Filtrasi Arang Sekam dan Arang Kayu terhadap Perubahan Parameter Fisika dan Kimia Limbah Domestik - Refanzah, Azril; Telaumbanua, Mareli; Amien, Elhamida Rezkia; Triyono, Sugeng (Jurnal Agricultural Biosystem Engineering, 2025)
Domestic wastewater pollution poses serious threats to public health and the environment, as it contains pollutants such as suspended solids, organic matter, ammonia, and dissolved substances that often exceed quality standards. Simple and low-cost treatment methods are therefore needed to improve wastewater quality before discharge. This study analyzed the quality of domestic wastewater before and after filtration using rice husk charcoal and wood charcoal as filter media. The observed parameters included physical indicators (temperature, TSS, TDS) and chemical indicators (pH, COD, BOD, NH₃). Filtration improved several physical parameters: TSS decreased, pH shifted closer to neutral, and temperature remained within the permissible deviation. In contrast, chemical parameters such as COD and BOD increased after treatment, likely due to the release of organic compounds from the charcoal media. Ammonia concentration also rose but stayed below the regulatory limit. Compared with the water quality standards of Lampung Province Regulation No. 11 of 2012 (Category I), only a few parameters met the requirements, particularly the physical indicators. Overall, rice husk and wood charcoal show potential as simple and inexpensive filter media for improving physical parameters of domestic wastewater. However, their effectiveness in reducing organic pollutants is limited, and integration with other treatment methods is recommended.